Acute effects of single and repeated mild traumatic brain injury on levels of neurometabolites, lipids, and mitochondrial function in male rats - Allen, Josh; Pham, Louise; Bond, Simon T.; O’Brien, William T.; Spitz, Gershon; Shultz, Sandy R.; Drew, Brian G.; Wright, David K.; McDonald, Stuart J. (Frontiers in Molecular Neuroscience, 2023)
Mild traumatic brain injuries (mTBIs) are the most common from of acquired brain injury. Symptoms of mTBI are thought to be associated with a neuropathological cascade, potentially involving the dysregulation of neurometabolites, lipids, and mitochondrial bioenergetics. Such alterations may play a role in the period of enhanced vulnerability that occurs after mTBI, such that a second mTBI will exacerbate neuropathology. However, it is unclear whether mTBI-induced alterations in neurometabolites and lipids that are involved in energy metabolism and other important cellular functions are exacerbated by repeat mTBI, and if such alterations are associated with mitochondrial dysfunction. In this experiment, using a well-established awake-closed head injury (ACHI) paradigm to model mTBI, male rats were subjected to a single injury, or five injuries delivered one day apart, and injuries were confirmed with a beam-walk task and a video observation protocol. Abundance of several neurometabolites was evaluated 24 hours post-final injury in the ipsilateral and contralateral hippocampus using in vivo proton magnetic resonance spectroscopy ( 1 H-MRS), and mitochondrial bioenergetics were evaluated 30 hours post-final injury, or at 24 hours in place of 1 H-MRS, in the rostral half of the ipsilateral hippocampus. Lipidomic evaluations were conducted in the ipsilateral hippocampus and cortex. We found that behavioral deficits in the beam task persisted 1-and 4-hours after the final injury in rats that received repetitive mTBIs, and this was paralleled by an increase and decrease in hippocampal glutamine and glucose, respectively, whereas a single mTBI had no effect on sensorimotor and metabolic measurements. No group differences were observed in lipid levels and mitochondrial bioenergetics in the hippocampus, although some lipids were altered in the cortex after repeated mTBI. The decrease in performance in sensorimotor tests and the presence of more neurometabolic and lipidomic abnormalities, after repeated but not singular mTBI, indicates that multiple concussions in short succession can have cumulative effects. Further preclinical research efforts are required to understand the underlying mechanisms that drive these alterations to establish biomarkers and inform treatment strategies to improve patient outcomes.